2022
DOI: 10.1101/2022.07.29.22278015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Germline genomic and phenomic landscape of clonal hematopoiesis in 323,112 individuals

Abstract: With age, acquired mutations can cause clonal expansion of hematopoietic stem cells (HSC). This clonal hematopoiesis of indeterminate potential (CHIP) leads to an increased predisposition to numerous diseases including blood cancer and cardiovascular disease. Here, we report multi-ancestry genome-wide association meta-analyses of CHIP among 323,112 individuals (19.5% non-European; 5.3% have CHIP). We identify 15 genome-wide significant regions and nominate additional loci through multi-trait analyses, and high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 96 publications
0
8
0
Order By: Relevance
“…16 CHIP was also recently assessed in participants of the UK Biobank by using exome sequencing data that have a limit of detection of ≈5% VAF, thus being at least 5-fold less sensitive than our method. 17,18 To enable a proper comparison with the UK Biobank prevalence rates, we adjusted for the sampling bias due to lower detection limit in our sample by downsampling our raw sequencing data to locus-specific exome sequencing coverage. We obtained the mean and SD of the coverage rates for each of the 32 genes that were present both in our panel and in the UK Biobank CHIP call (Table S2).…”
Section: Methodsmentioning
confidence: 99%
“…16 CHIP was also recently assessed in participants of the UK Biobank by using exome sequencing data that have a limit of detection of ≈5% VAF, thus being at least 5-fold less sensitive than our method. 17,18 To enable a proper comparison with the UK Biobank prevalence rates, we adjusted for the sampling bias due to lower detection limit in our sample by downsampling our raw sequencing data to locus-specific exome sequencing coverage. We obtained the mean and SD of the coverage rates for each of the 32 genes that were present both in our panel and in the UK Biobank CHIP call (Table S2).…”
Section: Methodsmentioning
confidence: 99%
“…The opposite effect directions observed at the CD164 locus for incident DNMT3A and TET2 CH could explain this null association in overall CH. Previously we and others reported opposite associations at the TCL1A locus with prevalent DNMT3A and TET2 CH, leading to a null association with overall CH 1,[13][14][15] . This study found an association at the TCL1A locus with incident overall CH and TET2 CH but not with incident DNMT3A CH.…”
Section: Discussionmentioning
confidence: 58%
“…This could be due to lower statistical power, poor imputation quality, or true biological differences between prevalent and incident CH. The CD164 locus is an example of the latter, where this locus is strongly associated with prevalent CH [13][14][15] but lacks any association with incident CH. The opposite effect directions observed at the CD164 locus for incident DNMT3A and TET2 CH could explain this null association in overall CH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 35 CHIP mutations were defined according to a prespecified list of pathogenic variants in 74 genes known to be drivers of clonal hematopoiesis and myeloid malignancies, as detailed in Table S2 . 36 , 37 To minimize false‐positive CHIP calls, variants were kept for further curation only if the total read depth was ≥10, 35 , 38 the read depth for the alternate allele was ≥3, and there was ≥1 read in both forward and reverse directions supporting the alternate allele. 35 CHIP was defined as variant allele frequency (VAF) ≥2%.…”
Section: Methodsmentioning
confidence: 99%